2013
DOI: 10.1007/s12325-013-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

C-QUALITY: Cost and Quality-of-Life Pharmacoeconomic Analysis of Antidepressants in Major Depressive Disorder in Italy

Abstract: The results indicate that escitalopram is the most cost-effective pharmacological treatment strategy for the Italian health service compared with other SSRIs and all SNRIs used in the first-line treatment of MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Only three of the reviewed studies that included DTs explicitly reported validation methods. Two used expert panels to validate the data sources and one used individual panellists to verify the model estimates [ 35 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only three of the reviewed studies that included DTs explicitly reported validation methods. Two used expert panels to validate the data sources and one used individual panellists to verify the model estimates [ 35 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, since the Italian health care system decentralizes the administrative decisions at regional level, creating several pricelists for each region, applying a weighted mean to the regional data is a common way of estimating national cost data 22. Moreover, in this case, the mean costs have been varied by means of probability distributions, with a PSA, in order to account for uncertainty in the model.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the DDC of escitalopram ranked fourth among antidepressants, but the high daily cost did not lessen the enthusiasm of patients. A cost and quality-of-life pharmacoeconomic analysis has also suggested that escitalopram, despite its tremendous cost, is preferred to other antidepressants as the most cost-effective pharmacological treatment strategy (9).…”
Section: Discussionmentioning
confidence: 99%
“…Drug utilization research has extensively been conducted to evaluate drug use in China, and a DDD as well as the daily drug cost (DDC) are popular concepts adopted in most drug utilization researches (8). Since patients with clinical depression require long-term treatment, it is important to take into account not only safety, tolerance, and therapeutic effects, but also costs of a drug (9). The DDC gives information about the average daily cost of a certain drug.…”
Section: Methodsmentioning
confidence: 99%